2015
DOI: 10.3368/npj.16.3.276
|View full text |Cite
|
Sign up to set email alerts
|

Conserving and restoring habitat for Greater Sage-Grouse and other sagebrush-obligate wildlife: the crucial link of forbs and sagebrush diversity

Abstract: Species Global •According to Garcia and others (2011) status Range Soils Community ranks and types Artemisia arbuscula Nutt. G5 CA, ID, MT, NV, Rocky, calcareous clays G2-G5 sage-steppe and grasslands ssp. arbuscula OR, UT, WA, WY or silt loams A. arbuscula ssp. longicaulis G4 CA, NV, OR Alluvial silts and sands Sage-steppe communities Winwood & McArthur on alluvial fans A. arbuscula ssp. longiloba G4 MT, WY Fine textured, shallow G3-G4 sage-steppe and (Osterh.) L.M. Shultz clay or silt loams stream terraces •… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 115 publications
0
30
0
Order By: Relevance
“…Restoration of A. tridentata after fires or other disturbances has been a management priority over the past decade, yet success of these efforts has been varied (Arkle et al., ; Knutson et al., ). Planting A. tridentata seed outside their adaptive breadth could result in unsuccessful establishment and/or low fitness and provide an opportunity for invasive species encroachment leading to a loss of species diversity and ecosystem degradation (reviewed in Dumroese, Luna, Richardson, Kilkenny, & Runyon, ). Previous research has shown that sagebrush species/subspecies are adapted to different ecological niches such as elevation and soil type (McArthur, ).…”
Section: Discussionmentioning
confidence: 99%
“…Restoration of A. tridentata after fires or other disturbances has been a management priority over the past decade, yet success of these efforts has been varied (Arkle et al., ; Knutson et al., ). Planting A. tridentata seed outside their adaptive breadth could result in unsuccessful establishment and/or low fitness and provide an opportunity for invasive species encroachment leading to a loss of species diversity and ecosystem degradation (reviewed in Dumroese, Luna, Richardson, Kilkenny, & Runyon, ). Previous research has shown that sagebrush species/subspecies are adapted to different ecological niches such as elevation and soil type (McArthur, ).…”
Section: Discussionmentioning
confidence: 99%
“…Defining target conditions for riparian restoration has been a challenge for land managers (van Diggelen et al 2001). Where improving wildlife habitat is a restoration objective, a common approach is to describe habitat conditions elsewhere that support desired wildlife populations, and then replicate those conditions through habitat manipulation (Dumroese et al 2015). Yet different wildlife species have unique habitat needs, potentially yielding an intractable number of species-specific restoration prescriptions that may not be mutually compatible (Mac Nally et al 2002, White et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…This represents about 15% of the regional flora (Dumroese et al . ). Over 30 plants are now in production for restoration purposes.…”
Section: Regional Initiativesmentioning
confidence: 97%